Doctoring with conviction: criminal records and the medical profession - Chamberlain, John Martyn (The British journal of criminology, 2018)
The General Medical Council decides if, when they are convicted of a crime, a doctor in the United Kingdom should be allowed to continue in their employment. This article is the first to detail these decisions for the period 2005–15. No doctor was barred from practising medicine for serious violent and sex offences, including rape, possession of images of child sexual abuse, manslaughter and domestic violence. These findings are placed in the context of contemporary developments in criminal record reform and criminological analysis of the relationship between employment and desistance. It is concluded that the high degree of devolved discretion allowed to elite professional occupations must be subjected to further critical scrutiny and policy reform.